Project Management And Succesful Entrepreneurship Venture In Nigeria - Obinna C, Iwueke; Njoku, Uche; Blessing N., Nwaiwu (Advances in Social Sciences Research Journal, 2017)
This paper takes an empirical look at project management and small business entrepreneurship venture operations in Nigeria. It posit that project management background is essential to the setting up and good performance of entrepreneurship venture. The lack of knowledge of project management can create problems that will affect entrepreneurship venture growth and achievement of desirable objectives that lead to economic growth and development. The data used for the study was mainly from primary source through the use of questionnaire and personal interview and was complemented by secondary data. The study used Pearson chi- square statistical tools to analyses the data. The empirical results revealed that project management is not given adequate attention in the startup and operation of entrepreneurship ventures, this was attributed to lack of skills, knowledge and abilities and ignorance in the are a of project management by individuals and institutions. Furthermore, the study established that some of the project management practices, approaches, competencies, and project managers ’ personal characteristics abound but how to apply them in entrepreneurship venture operations is a problem. The conclusion is that all stakeholders involved in entrepreneurship and business processes in Nigeria should be grounded in the basic elements of project management and know- how to apply them in entrepreneurship ventures. Recommendations are provided on how to galvanize the two concepts into desired results that will facilitate maximum results.